Phospholipid Binding Protein C Inhibitor (PCI) Is Present on Microparticles Generated In Vitro and In Vivo. - Katrin Einfinger; Sigrun Badrnya; Margareta Furtmüller; Daniela Handschuh; Herbert Lindner; Margarethe Geiger (PLoS ONE)
Protein C inhibitor is a secreted, non-specific serine protease inhibitor with broad protease reactivity. It binds glycosaminoglycans and anionic phospholipids, which can modulate its activity. Anionic phospholipids, such as phosphatidylserine are normally localized to the inner leaflet of the plasma membrane, but are exposed on activated and apoptotic cells and on plasma membrane-derived microparticles. In this report we show by flow cytometry that microparticles derived from cultured cells and activated platelets incorporated protein C inhibitor during membrane blebbing. Moreover, protein C inhibitor is present in/on microparticles circulating in normal human plasma as judged from Western blots, ELISAs, flow cytometry, and mass spectrometry. These plasma microparticles are mainly derived from megakaryocytes. They seem to be saturated with protein C inhibitor, since they do not bind added fluorescence-labeled protein C inhibitor. Heparin partially removed microparticle-bound protein C inhibitor, supporting our assumption that protein C inhibitor is bound via phospholipids. To assess the biological role of microparticle-bound protein C inhibitor we performed protease inhibition assays and co-precipitated putative binding partners on microparticles with anti-protein C inhibitor IgG. As judged from amidolytic assays microparticle-bound protein C inhibitor did not inhibit activated protein C or thrombin, nor did microparticles modulate the activity of exogenous protein C inhibitor. Among the proteins co-precipitating with protein C inhibitor, complement factors, especially complement factor 3, were most striking. Taken together, our data do not support a major role of microparticle-associated protein C inhibitor in coagulation, but rather suggest an interaction with proteins of the complement system present on these phospholipid vesicles.